Recovering Pacific rockfish at risk: the economic valuation of management actions - Keldi Forbes; Peter C. Boxall; Wiktor L. Adamowicz; Alejandro De Maio Sukic (Frontiers in Marine Science, 2015)

An Econometric Analysis of the Effect of Forest Dependence on the Economic Well-Being of Canadian Communities - Nancy Leake; Wiktor L. Adamowicz; Peter C. Boxall (Forest Science, 2006)
This study examines how changes in economic activity in forestry, expressed as forest dependence at a census subdivision level (CSD), affected measures of economic well-being. The empirical models used to address this question were developed and estimated using random effects panel and two-stage least-squares estimators using data from the 1986, 1991, and 1996 Canadian census. The results illustrate the contribution of economic diversity to income growth and poverty reduction. However, the results also suggest that forest dependence was positively and significantly related to unemployment rates and to the incidence of poverty for people in private households. Forest dependence was shown to have little or no effect on median household income and the distribution of income within CSDs. These relationships were assessed while holding constant other factors expected to affect community level economic well-being, including economic diversity, trade exposure, and aggregate demand.

Modeling Opportunity Costs of Conservation in Transitional Landscapes - ROBIN NAIDOO; WIKTOR L. ADAMOWICZ (Conservation Biology, 2006)
Conservation scientists recognize the urgency of incorporating opportunity costs into conservation planning. Despite this, applications to date have been limited, perhaps partly because of the difficulty in determining costs in regions with limited data on land prices and ownership. We present methods for estimating opportunity costs of land preservation in landscapes or ecoregions that are a changing mix of agriculture and natural habitat. Our approach derives from the literature on estimating land values as opportunity costs of alternate land uses and takes advantage of general availability of necessary data, even in relatively data‐poor regions. The methods integrate probabilities of habitat conversion with region‐wide estimates of economic benefits from agricultural land uses and estimate land values with a discount rate to convert annual values into net present values. We applied our method in a landscape undergoing agricultural conversion in Paraguay. Our model of opportunity costs predicted an independent data set of land values and was consistent with implicit discount rates of 15–25%. Model‐generated land values were strongly correlated with actual land values even after correcting for the effect of property size and proportion of property that was forested. We used the model to produce a map of opportunity costs and to estimate the costs of conserving forest within two proposed corridors in the landscape. This method can be applied to conservation planning in situations where natural habitat is currently being converted to market‐oriented land uses. Incorporating not only biological attributes but also socioeconomic data can help in the design of efficient networks of protected areas that represent biodiversity at minimum costs.

Incorporating Natural Capital into Economy-Wide Impact Analysis: A Case Study from Alberta - Mike N. Patriquin; Janaki R. R. Alavalapati; Wiktor L. Adamowicz; William A. White (Environmental Monitoring and Assessment, 2003)

Coarse Filter Ecosystem Management in a Nonequilibrating Forest - Glen W. Armstrong; Wiktor L. Adamowicz; James A. Beck; Steven G. Cumming; Fiona K.A. Schmiegelow (Forest Science, 2003)
The natural disturbance model of forest management is the basis of many of the sustainable forest management systems being proposed for the boreal forest of Canada. Wildfire is the dominant natural agent of disturbance in the boreal mixed-wood forest. The natural disturbance model assumes that timber harvesting systems emulating the annual area burned by natural fire, its spatial distribution, and the amount of residual material can be developed. It is further assumed that natural processes can be emulated closely enough to maintain forest biota at natural or near-natural population levels. This is a coarse filter approach to ecosystem management. In order to emulate the natural rate of disturbance, one needs to quantify it. The annual area burned in the study area, under natural conditions, is characterized as a random draw from a lognormal distribution. A modeling system comprised of an aspatial Monte Carlo simulation model and a linear programming based forest activity scheduling model was developed. The simulation model is used to develop 200 yr forecasts of probability distributions for habitat area of five vertebrate species under a stochastic wildfire regime. These probability distributions are used to construct habitat area constraints for use in an optimization model to help quantify the trade-offs between timber values and maintenance of the range of natural variability in the forest. The model is used to identify the trade-offs between forest harvesting, wildlife habitat, and the degree of similarity between the managed forest structure and the distribution of structures that could be generated by natural disturbance. FOR. SCI. 49(2):209–223.

Effects of Economic Prosperity on Numbers of Threatened Species - Robin Naidoo; Wiktor L. Adamowicz (Conservation Biology, 2001)
We used data from over 100 countries to investigate the link between numbers of threatened species and per‐capita gross national product. We corrected for factors that might otherwise confound such a relationship. Our study was motivated by the continuing debate over the relationship between environmental degradation and per‐capita income. Proponents of the environmental Kuznets‐curve hypothesis argue that although environmental degradation may increase initially, increases in per‐capita income will eventually result in greater environmental quality. Theoretical objections and the lack of widespread empirical evidence recently have thrown doubt on the existence of such a pattern. Treating threat to biodiversity as one potential indicator of environmental degradation, we divided threatened species into seven taxonomic groups ( plants, mammals, birds, amphibians, reptiles, fishes, and invertebrates) and analyzed each group separately. Count‐data regression analysis indicated that the number of threatened species was related to per‐capita gross national product in five of seven taxonomic groups. Birds were the only taxonomic group in which numbers of threatened species decreased throughout the range of developed countries' per‐capita gross national product. Plants, amphibians, reptiles, and invertebrates showed increasing numbers of threatened species throughout this same range. If these relationships hold, increasing numbers of species from several taxonomic groups are likely to be threatened with extinction as countries increase in prosperity. A key challenge is to understand the interactions among consumer preferences, biology, and institutions that lead to the relationship observed for birds and to see whether this knowledge can be applied to conservation of other taxa.

Distributive Impacts of Forest Resource Policies in Alberta - Janaki R. R. Alavalapati; Wiktor L. Adamowicz; William A. White (Forest Science, 1999)
Economy-wide and distributive impacts of: (1) an $80 million increase in pulp and paper exports; (2) a $10 million decrease in lumber exports; (3) a 25% increase in the costs of timber production; and (4) a 25% increase in the costs of pulp and paper production in Alberta's forest sector are examined. A social accounting matrix (SAM)-based quantity model is used to examine the first two shocks, while a SAM-based price model is used to analyze the last two shocks. The results of the quantity model suggest that higher income households get a larger share of the benefits than lower income households in response to an expansion in the pulp and paper industry. A contraction in the lumber sector will hurt higher income households more than lower income households. Larger shares of medium and higher income households in total labor income and capital rents are identified as reasons for this asymmetric response. The results of the price model suggest that additional costs associated with sustainable forest management and environmental regulations will hurt lower income households more than higher income households. The higher share of consumer expenditure in total income for lower income households when compared to that of high income households may be responsible for this result. For. Sci. 45(3):342-348.